PENGEMBANGAN BUKU CERTAGAM UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN PADA SISWA KELAS II SD NEGERI PULUTAN 02 - Ana Septianingsi; Henny Dewi Koeswanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop a picture storybook called Certagam as an instructional medium to improve reading comprehension skills of second-grade students at SD Negeri Pulutan 02. The research used a Research and Development (R&D) method based on the ASSURE model. The development process included three main stages: preliminary study, product development, and limited trial. Data collection instruments included expert validation (material, media, and design) as well as pretest and posttest among students. The validation results showed that the Certagam book received a